Catholic Priest’s Role in Disseminating Books in Lithuanian Language (Based on Correspondence to Zawadzki’s Publishing House in Wilno). - Kowkiel, Lilia; Pacevičius, Arvydas (Bibliotheca Lituana, 2012)
This article discusses examples of cooperation between the representatives of the Zawadzki publishing house in Wilno and catholic priests involved in distribution of books in the Lithuanian language in the Lithuania lands in mid-19th century. The sources of information are handwritten materials held in the Lithuanian State Historical Archives of Vilnius. Main object of publication are letters of catholic priests working in parishes, where Lithuanians dominate among the religious population. The article will also mention catholic priests from the Diocese of Samogitia – Jan Cyparewicz (Utena), Jan Darzyński (Kriaunos), Jacewicz (Anykščiai), Antoni Juszkiewicz (Vilkija), Jan Pacewicz (Užpaliai), Józef Sokołowski (Antazavė), Gustaw Tomkiewicz (Šiauliai), Szymon Warkałło (Šakiai). Their role was very important because catholic priesthood in the middle of 19th century belonged to the core group that formed intelligentsia from which originated a big part of activists in the Lithuanian national movement.